2020
DOI: 10.2147/jpr.s264101
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prediction of Postoperative Pain and Opioid Consumption Using Intraoperative Surgical Pleth Index After Surgical Incision: An Observational Study</p>

Abstract: Background: We evaluated whether the surgical pleth index (SPI) following surgical incision was related to postoperative pain and opioid consumption. Methods: This prospective observational study was performed in 50 patients undergoing laparotomy under sevoflurane-based general anesthesia. We recorded the highest SPI during surgical incision. The postoperative pain with a numerical rating scale (NRS) and opioid consumption during postoperative 24 h were compared in patients who showed SPI over 50 (Group H) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…It is well-known that SPI derived from the analysis of the plethysmographic pulse wave amplitude and interval could reflect the different levels of autonomous nerve system activation, which is often caused by pain stimulation. Mounting studies have shown that SPI has the potential to reflect intraoperative noxious stimulation and guide the administration of opioids in adult patients ( 10 , 11 ), and the cut-off value of 50 was used to distinguish between mild and moderate-to-severe pain ( 12 ). However, different from adult patients, the study by Ledowski et al showed that the cut-off value of SPI 50 may be too high to predict acute postoperative pain in children, and its use in children may cause more postoperative agitation and fentanyl consumption ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that SPI derived from the analysis of the plethysmographic pulse wave amplitude and interval could reflect the different levels of autonomous nerve system activation, which is often caused by pain stimulation. Mounting studies have shown that SPI has the potential to reflect intraoperative noxious stimulation and guide the administration of opioids in adult patients ( 10 , 11 ), and the cut-off value of 50 was used to distinguish between mild and moderate-to-severe pain ( 12 ). However, different from adult patients, the study by Ledowski et al showed that the cut-off value of SPI 50 may be too high to predict acute postoperative pain in children, and its use in children may cause more postoperative agitation and fentanyl consumption ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in 2013, Gruenewald et al [ 5 ] proposed a ∆SPI >10 or an absolute SPI value >50 as a predictor of inadequate analgesia. In other studies, only an absolute value of ∆SPI >50 was an indication for rescue analgesia [ 11 ]. In the methodology of the current study, a compromising protocol of ∆SPI >15, compared to the calculated baseline during Stage 2 and lasting at least one minute, was adopted as an indicator for rescue analgesia to avoid a potentially hazardous overdosage of FNT as a result of a potential miscalculation of the SPI score due to its variations.…”
Section: Methodsmentioning
confidence: 99%
“…The adequacy of anaesthesia (AoA), comprising the monitoring of RE, SE, NMT, and SPI, is crucial in assessing the quality of anaesthesia [ 7 ]. So far, we have published the current study findings regarding the influence of the employment of AoA guidance on GA with different PA techniques in patients undergoing VRS on the incidence of postoperative pain and perioperative haemodynamic stability [ 8 , 9 , 10 , 11 ] as preliminary reports. Currently, we investigate the intraoperative efficacy of various PA techniques, which are detected indirectly by observations of variations in SPI values, as an indication for IROA using FNT during various stages of VRS performed under AoA guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Jung et al [40] evaluated whether the highest SPI during surgical incision was related to postoperative pain and opioid consumption. They recorded the highest SPI during surgical incision, and postoperative NRS scores for pain and opioid consumption during postoperative 24 h were compared between patients with SPI > 50 or 20-50.…”
Section: Spi Monitoring For the Prediction Of Postoperative Pain And ...mentioning
confidence: 99%